Co-creating a service ecosystem for supporting digitalization in health and welfare - Hannu Tikkanen; Ruusa Ligthart; Anna Salmi; Outi Ahonen (Finnish Social and Health Informatics Association, 2024)
Health and welfare services are increasingly striving towards data-driven, digital and patient-centric approaches to service management and delivery. The growing digitalization and amount of eHealth services introduced are part of a sociotechnical change in health and social care, where different sectors collaborate in ecosystems. This study focuses on ecosystemic collaboration in health and welfare and its potential in value creation, with a particular interest in how multistakeholder co-creation can be enabled and orchestrated. The study draws on research on service ecosystem design, open innovation and co-creation. The aim of this study is to explore how service ecosystems are co-created by public, private and third-sector organizations in the health and welfare sector. To achieve this aim, our study has two research objectives. First, the study explores current ecosystemic practices in health and welfare. Second, the study identifies factors that affect these practices. This study presents the findings of a qualitative study conducted in Finland in spring 2023 with key informants from the health and welfare sector. The study context revolves around a HEI that provides university level teaching in social and health care and adopts a problem-based pedagogy that is firmly grounded in working-life collaboration with cross-sectoral actors and professional practice in the field. The findings reveal different factors that have an effect on ecosystem collaboration. The findings support the argument that working in ecosystems is beneficial and digitalization has been a key driver of innovation in the health care and welfare sector in Finland. Based on these findings, we discuss the potential of orchestrators, such as HEIs, to co-create service ecosystems that enable digitalization of health and welfare.